PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING PADA PELAJARAN SENI BUDAYA DI SMP NEGERI 29 PADANG - Harmawan, Yosdikha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The implementation of the quantum teaching model, which prioritizes learning for pleasure, is expected to increase learning efficiency so that more optimal learning results are achieved. This study intends to determine the extent to which the effectiveness of student learning increases after the implementation of the quantum teaching model in the Art and Culture course at SMP N 29 Padang. The method of this study used a quasi-experimental design with one group pretest-posttest. Class VII.5 students of SMPN 29 Padang, totaling 35 students, were the subjects of this study. The results of the study show an increase in learning effectiveness, which is quite good with a normalized average gain value of 0.648 with moderate criteria.